APPLICATING SENSEMAKING FRAMEWORK METHOD IN EXPLORATION OF COLORWAY FOR DESIGNER TOYS - Adhika, Fauzi Arif; Lestari, Intan Suci (Prodi Teknologi Pendidikan, 2024)
This research examines the use of various colorways by toy designers to develop new lines while keeping the same product form. This approach aims to increase consumer appeal by offering a variety of color choices while reducing production costs. This study explores how toy designers use colorway strategies to adapt (characteristics) popular characters. These strategies are analyzed using the sensemaking framework method by Dinçer to understand their impact on marketing and consumer interest. The research results show that using (thematic) coloring variations not only increases productivity but also broadens the market appeal of designer toys, highlighting the significant role of color in design and marketing.